Inactivation of COX-2, HMLH1 and CDKN2A Gene by Promoter Methylation in Gastric Cancer: Relationship with Histological Subtype, Tumor Location and Helicobacter pylori Genotype - Santos Alves, Markenia Kelia; Ferrasi, Adriana Camargo [UNESP]; Lima, Valeska Portela; Pitombeira Ferreira, Marcia Valeria; Pardini, Maria Ines de Moura Campos [UNESP]; Barem Rabenhorst, Silvia Helena (Karger, 2011)
Objective: We aimed to evaluate the inactivation of COX-2, HMLH1 and CDKN2A by promoter methylation and its relationship with the infection by different Helicobacter pylori strains in gastric cancer. Methods: DNA extracted from 76 H. pylori-positive gastric tumor samples was available for promoter methylation identification by methylation-specific PCR and H. pylori subtyping by PCR. Immunohistochemistry was used to determine COX-2, p16(INK4A) and HMLH1 expression. Results: A strong negative correlation was found between the expression of these markers and the presence of promoter methylation in their genes. Among cardia tumors, negativity of p16(INK4A) was a significant finding. on the other hand, in noncardia tumors, the histological subtypes had different gene expression patterns. In the intestinal subtype, a significant finding was HMLH1 inactivation by methylation, while in the diffuse subtype, CDKN2A inactivation by methylation was the significant finding. Tumors with methylated COX-2 and HMLH1 genes were associated with H. pylori vac A s1 (p = 0.025 and 0.047, respectively), and the nonmethylated tumors were associated with the presence of the gene flaA. Conclusions: These data suggest that the inactivation of these genes by methylation occurs by distinct pathways according to the histological subtype and tumor location and depends on the H. pylori genotype. Copyright (C) 2011 S. Karger AG, Basel
Keywords: Gastric cancer; Histological subtypes; Tumor location; Methylation; p16 (INK4A); HMLH1; COX-2; Helicobacter pylori genotypes